PENGARUH INVESTASI, ANGKATAN KERJA DAN PENGELUARAN PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI SUMATERA BARAT - Efrizal Hasan; Syamsul Amar (Jurnal Riset Manajemen Bisnis dan Publik, 2013)
This study aims to analyze 1) the effect of investment on economic growth in the province of West Sumatra, 2) The effect of labor force on the economic growth in the province of West Sumatra, 3) The effect of government spending on economic growth in the province of West Sumatra, 4) Influence of investment, labor force and government expenditures together on economic growth in the province of West Sumatera. Research conducted an exploratory study in the area of West Sumatra province, to see an image of the effect of investment, labor force and government expenditures on economic growth in West Sumatra during the period 1981-2010. Data analysis technique area used to prove and test the hypothesis propose disnon linear regression. The result showed that the investment variable, labor force and government expenditures have a positive and significant impact on economic growth in the province of West Sumatra. This means that if there is an increase in investment, the number of labor force and increase government spending can trigger economic growth in West Sumatra. Keywords: investment, effect of labor force, government spending, Influence of investment